Temporomandibular Joint Pain Dysfunction Syndrome: Characteristics of Its Complex of Symptoms; Effectiveness of Traditional Treatment Supplemented by Neurologist Recommendations - N. Lytovchenko; D. Gushcha (Львівський клінічний вісник, 2025)
Introduction. Temporomandibular joint (TMJ) dysfunction is a pathological condition that does not allow the maxillofacial system to function properly and is determined with a high frequency among the population, including young people. Nowadays, many theories of the origin of dysfunction are considered: occlusion disorders, muscle imbalance, psychoneurological disorders. The picture of clinical manifestations of TMJ dysfunction is often accompanied by pain and is determined by many factors, which greatly complicates diagnosis and treatment. This indicates the need for further in-depth study of temporomandibular joint dysfunction, which determined the relevance and created the prerequisites for this study.